Assessment of leachables and extractables in “super-swelling” hydrogel-forming microarray patches - Qonita Kurnia Anjani; Peter E. McKenna; Eneko Larrañeta; Panagiotis Manesiotis; Yidan Luo; Masoud Adhami; Fabiana Volpe-Zanutto; Gareth Orr; Sabrina Roussel; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Hydrogel-forming microarray patches (MAPs) offer a minimally invasive platform for transdermal drug delivery, enabling systemic absorption of active pharmaceutical ingredients. Unlike dissolving MAPs, which deposit their entire polymer matrix into the skin, hydrogel-forming MAPs remain intact upon removal, reducing polymer exposure while delivering higher drug doses than dissolving or coated MAPs. Moreover, they have demonstrated excellent biocompatibility and do not cause skin or systemic issues, even with repeated application in humans. This study assessed the leachable and extractable compounds from hydrogel-forming MAPs composed of Gantrez ® S-97, PEG 10,000, and sodium carbonate under various conditions. Under physiological conditions (37°C in water), minimal PEG 10,000 leaching (10.4 ± 2.0%) and negligible Gantrez ® S-97 extraction (< 2%) confirmed the hydrogel matrix’s stability and safety. However, stress testing in DMSO at 70°C led to increased PEG 10,000 extraction (up to 32.9 ± 6.1%) and minor Gantrez ® S-97 degradation, likely due to ester hydrolysis. These findings highlight the robustness of hydrogel-forming MAPs, ensuring minimal systemic exposure to unbound polymers while maintaining effective drug delivery. The results support their potential for chronic therapeutic applications requiring repeated dosing. Further clinical studies are needed to validate these findings, facilitating regulatory approval and broader adoption across diverse medical applications. Graphical Abstract